2021
DOI: 10.1177/0300060521992215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory role of circRNA_100395 in the proliferation and metastasis of prostate cancer cells

Abstract: Objective Circular RNAs (circRNAs) are non-coding RNAs with high cancer-specific expression and the potential for regulating tumorigenesis. CircRNA_100395 is expressed at low levels in many cancers and is involved in the regulation of tumor cell proliferation and metastasis. However, its expression and function in prostate cancer remain unclear. Methods Endogenous expression levels of circRNA_100395 and microRNA-1228 (miR-1228) in prostate cancer tissue samples and cell lines were detected by quantitative reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For instance, up-regulated circZMIZ1 has been revealed to facilitate the proliferation of PCa cells and is a potential biomarker for PCa treatment [ 27 ]. The suppressive role of circRNA_100395 in the proliferation and metastasis of PCa cells has also been discovered recently [ 28 ]. In this study, circSERPINA3 was found to be overtly up-regulated in PCa cells compared to normal WPMY-1 cells by means of RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, up-regulated circZMIZ1 has been revealed to facilitate the proliferation of PCa cells and is a potential biomarker for PCa treatment [ 27 ]. The suppressive role of circRNA_100395 in the proliferation and metastasis of PCa cells has also been discovered recently [ 28 ]. In this study, circSERPINA3 was found to be overtly up-regulated in PCa cells compared to normal WPMY-1 cells by means of RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence manifests the important involvement of circRNA dysregulation in different types of human tumors. He et al (2021) find the downregulation of circRNA_100395 in prostate cancer, and they clarified that cell metastasis was inhibited by circRNA_100395. Chen et al (2021) attest that the level of circ_0001360 in cutaneous squamous cell carcinoma was decreased, and the overexpression of circ_0001360 repressed the carcinogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…circRNA_100146 is significantly upregulated in prostate cancer cells, and circRNA_100146 silencing can inhibit their invasion, migration, and proliferation [ 14 ]. Overexpression of circRNA_100395 inhibits the proliferation of prostate cancer cells, alters the distribution of cell cycle phases, reduces cell migratory and invasive ability, and inhibits EMT, making it a potential therapeutic target for prostate cancer [ 15 ]. In our study, circSPECC1 was derived from the SPECC1 parent gene and formed a loop.…”
Section: Discussionmentioning
confidence: 99%